Боротьба Української повстанської армії проти колективізації західноукраїнського села (1944-1952 рр.) - Сеньків, Михайло; Senkiv, Mykhailo (Східноєвропейський національний університет імені Лесі Українки, 2014)
Показано, що найбільш гострою формою боротьби селянства проти колективізації була їх участь у збройних формуваннях УПА, куди селяни масово вступали, творячи її соціальну базу. Проаналізовано форми, методи та засоби боротьби Української повстанської армії проти колективізації західноукраїнського села.

In the article it has been shown that the peasants’ struggle in the armed forces of the UPA (the Ukrainian Insurgent Army) against the collectivization of the village in 1944-1952 was their struggle in its acutest form. The peasants became the members of the UPA (the Ukrainian Insurgent Army), creating its social base. It has been analysed forms, methods and means of the UPA’s struggle against the collectivization of the West-Ukrainian village.
The Struggle of the UРА (the Ukrainian Insurgent Army) against the Collectivization of the West-Ukrainian Village (1944–1952)
Keywords: західноукраїнське селянство; боротьба; колективізація; депортації; збройні формування ОУН-УПА; the West-Ukrainian peasantry; the struggle; the collectivization; the armed forces of OUN–UPA